Pengaruh Gaya Kepemimpinan Dan Kompensasi Terhadap Kinerja Pegawai Pada Royal Senyiur Hotel Kabupaten Pasuruan - Syafiudin, Ilham; Rachma, N.; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2025)
Abstrack This study was conducted to determine the influence of leadership and compensation on employee performance at the Royal Senyiur Hotel in Pasuruan Regency. This study is quantitative. The data collection method used in this study was a questionnaire distributed directly at the Royal Senyiur Hotel to a sample of 32 respondents and tested for validity and reliability. Data analysis used IBM SPSS Statistics Version 23. The data analysis method used multiple linear regression analysis. The results obtained from this study prove that leadership style does not have a significant impact on employee performance. Compensation has a positive and significant effect on employee performance. (3) Leadership style and compensation have a positive and significant effect on employee performance. The results of this study indicate that leadership style and compensation together have a positive and significant impact on employee performance. Leadership style does not significantly influence employee performance at the Royal Senyiur Hotel in Pasuruan Regency. The adjusted R-square value in this study was 0.752, indicating that 75.2% of the Employee Performance variable can be explained by Leadership Style and Compensation, while the remaining 24.8% is influenced by other variables. Keywords: Leadership, Compensation, Employee Performance